2018
DOI: 10.1080/07420528.2018.1466794
|View full text |Cite
|
Sign up to set email alerts
|

Examining courses of sleep quality and sleepiness in full 2 weeks on/2 weeks off offshore day shift rotations

Abstract: To better understand sleep quality and sleepiness problems offshore, we examined courses of sleep quality and sleepiness in full 2-weeks on/2-weeks off offshore day shift rotations by comparing pre-offshore (1 week), offshore (2 weeks) and post-offshore (1 week) work periods. A longitudinal observational study was conducted among N=42 offshore workers. Sleep quality was measured subjectively with two daily questions and objectively with actigraphy, measuring: time in bed (TIB), total sleep time (TST), sleep la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 57 publications
0
21
0
Order By: Relevance
“…This can be a significant factor impairing monitoring performance and reducing alertness levels. The impact of disturbed circadian rhythms would have a negative impact on sleep quality, which, in turn, could result in increased chronic fatigue (Barton, Spelten, Totterdell, Smith, & Folkard, 1995) and negatively influence alertness and task performance (Riethmeister, Bültmann, De Boer, Gordijn, & Brouwer, 2018). The nature of ATCOs’ shift work induces circadian dysrhythmia and can cause the breakdown of arousal and activation that can impair ATCOs’ performance if this breakdown is not be corrected by effort (Pribram & McGuinness, 1975; Sanders, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…This can be a significant factor impairing monitoring performance and reducing alertness levels. The impact of disturbed circadian rhythms would have a negative impact on sleep quality, which, in turn, could result in increased chronic fatigue (Barton, Spelten, Totterdell, Smith, & Folkard, 1995) and negatively influence alertness and task performance (Riethmeister, Bültmann, De Boer, Gordijn, & Brouwer, 2018). The nature of ATCOs’ shift work induces circadian dysrhythmia and can cause the breakdown of arousal and activation that can impair ATCOs’ performance if this breakdown is not be corrected by effort (Pribram & McGuinness, 1975; Sanders, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of participants in the studies were men (averagely 91.2%), and all were aged between 16 and 68 years (mean of study means=39.23±4.29 years). The majority (89.25%) of studies were rated medium to high on the JBI Quality Rating Scale: 58 of 90 studies, for example, [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] rated ≥70% (high), 23 studies, for example, 18 44-49 rated 50%-69% (medium), and 9 studies, for example, 17 50-57 rated <50% (low) (table 1).…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…As daily measurements were administered for 28 days, this resulted in 1008 total measures for both PA and sleepiness. Additional information about the study can be found elsewhere [ 17 , 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…In an earlier study, we demonstrated that especially self-reported fatigue increased during the offshore period [ 17 ]. In addition, workers slept less whilst offshore, rated their sleep quality lower, and felt less refreshed after awakening [ 18 ]. A relatively high work load, shift work, and long work hours are characteristics of the offshore work environment associated with higher fatigue levels [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%